Optimization of Al-Qur’an Learning in Gen Z (Case Study of Bittuqo Method at Bpui Minhajut Thulab Banyuwangi) - Masruri, M. Sauqi Iza; Kawakip, Akhmad Nurul; Yahya, Mokhammad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This journal discusses the importance of optimizing Qur’an learning in Indonesia, especially for generation Z, through the implementation of the Bittuqo Method at the BPUI Minhajut Thulab Krikilan Banyuwangi Islamic Boarding School. The Qur’an as a guide to life for Muslims requires a deep understanding, and effective learning methods are needed to improve Qur’an literacy among the community, especially amidst the challenges of the characteristics of the younger generation who want instant results. The Bittuqo Method, which combines reading and writing skills, is systematically designed to achieve the ability to read the Qur’an in a short time. This study uses a qualitative approach with case studies to explore the application of the method. The results show that this method not only provides an interesting and relevant learning experience, but also helps students internalize the values ??of the Qur’an. With a structured evaluation, students are motivated to improve their ability to read and understand the teachings of the Qur’an, so that they are expected to be a generation with Qur’anic character and ready to face future challenges. This study makes a significant contribution to the development of relevant Qur’an education for generation Z.